2014
DOI: 10.1038/ncomms5804
|View full text |Cite
|
Sign up to set email alerts
|

Small GTPase Rab37 targets tissue inhibitor of metalloproteinase 1 for exocytosis and thus suppresses tumour metastasis

Abstract: Rab small GTPases are master regulators of membrane trafficking and guide vesicle targeting. Recent publications show that Rab-controlled trafficking pathways are altered during tumorigenesis. However, whether any of the Rabs plays a metastasis suppressor role is least explored. Here we address the metastasis suppressive function of human Rab37 (hRAB37) using secretomics, cell, animal and clinical analyses. We show that tissue inhibitor of metalloproteinase 1 (TIMP1), a secreted glycoprotein that inhibits extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 46 publications
3
52
0
1
Order By: Relevance
“…Rab37 was found by Tsai's group downregulated in lung cancer patients with metastasis, which was associated with the worse outcome. Further investigation revealed that Rab37 targeted tissue TIMP-1 for exocytosis and in turn inhibits cancer metastasis [22]. Additionally, Okon and his colleagues found that Rab7 inhibited angiogenesis through regulating neuropilin-1 degradation in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Rab37 was found by Tsai's group downregulated in lung cancer patients with metastasis, which was associated with the worse outcome. Further investigation revealed that Rab37 targeted tissue TIMP-1 for exocytosis and in turn inhibits cancer metastasis [22]. Additionally, Okon and his colleagues found that Rab7 inhibited angiogenesis through regulating neuropilin-1 degradation in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported that Rab37 was a metastasis suppressor . Here, we provide compelling evidence from cell‐based, animal and clinical studies that Rab37 functions as a modulator of macrophage polarization via regulating the exocytosis of sST2, resulting in the preferential shift of macrophages phenotype from M2‐like to M1‐like, and thereby inhibiting tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The stable empty vector (EV), Rab37‐wild type (WT), GTP‐bound constitutive active (Q89L) or GDP‐bound dominant negative (T43N) cells were generated as described previously . The shRNA lentivirus for Rab knockdown, shRab#1, shRab#2 or sh‐ST2 was obtained from the National RNAi core Facility (Institute of Molecular Biology, Academia Sinica, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Rab 25 and chloride intracellular channel 3 (CLIC3) drives invasiveness of pancreatic and ovarian cancer by regulating the recycling of α5β1 integrin from late endosomes to the plasma membrane [160]. In contrast, Rab37 suppresses tumour metastasis by exocytosis of the tissue inhibitor of metalloproteinase 1 (TIMP1), thereby inhibiting matrix metalloproteinase 9 (MMP9) [161]. Finally, Rab18 is highly expressed in Hepatitis B virus (HBV)-associated HCC tissue and upregulated Rab18 is mediated by HBV X protein, which promotes hepatoma cell proliferation [162].…”
Section: The Role Of Gtpase During Cytokinesis and Viral Buddingmentioning
confidence: 99%